Evaluation of Antioxidant Potential and Phytochemical Composition of Carrageenan Extracts from Nine Edible Seaweed Species - Katrin Mae Mendoza Ortega; Eric Camilo Rubia Punzalan; Ma Carmen Ablan Lagman (Borneo Journal of Pharmacy, 2026)
Seaweeds have become a subject of interest due to their dual role, not only in providing functional attributes, such as gelling, thickening, and stabilizing in food products, but also for their potential antioxidant properties. Currently, a growing body of research supports the idea that supplementation with antioxidants is a valuable approach in preventing oxidative stress, which can lead to cancer, diabetes, cardiovascular, and neurological diseases, where free radicals are implicated. This study aimed to determine the antioxidant activity and phytochemical composition of carrageenan extracts from nine algae collected from the Western Visayas region. Antioxidant activity was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, and the phytochemical composition was analyzed by thin-layer chromatography. Eight of the nine algal extracts exhibited antioxidant activity. The most active extracts were observed in S. crassifolium (IC50 = 559 μg/mL), followed by S. moniliformis (IC50 = 573 μg/mL) and E. muricatum (IC50 = 629 μg/mL), with no significant difference from the positive control. The abundance of flavonoids, phenols, alkaloids, saponins, tannins, steroids, essential oils, and other phenolic compounds was observed across all extracts, indicating significant antioxidant activity. These findings imply that the integration of natural antioxidants from algae as a dietary supplement could prove beneficial in mitigating oxidative stress, thus holding significance in a wide array of disease prevention strategies, such as cancer, diabetes, cardiovascular diseases, and neurological disorders, all of which are intricately linked to the role of free radicals.